THE CONNECTION BETWEEN THE TYPE AND COLOR OF THE SEEDS AND THE AGRONOMIC VALUABLE TRAITS OF F5 HYBRIDS OF G.BARBADENSE L. (European Journal of Interdisciplinary Research and Development, 2025)
The research results showed that, we could conclude that the type and color of seeds do not significantly affect the main of agronomic valuable traits. There was a weak correlation between some traits. The type and color of the undercut can be used as a marker attribute in breeding.